The yield and biological activity (LC50) of rotenone extracted from Derris elliptica - Zubairi, Saiful Irwan (2006)
The objective of this research was to determine the effect of the processing parameters on the extraction yield of rotenoids resin, rotenone and their biological activities (LC50). The research was divided into three stages: preliminary, optimization and verification phases. Preliminary study was carried out to determine the most appropriate processing parameters for the optimization study. The optimization study was carried out using a Central Composite Design (CCD) employing the Design-ExpertÂ® software version 6.0 to determine the effects of processing parameters on the three selected response variables which were the yield of rotenoids resin, yield of rotenone and biological activity (LC50) of rotenoids resin. The processing parameters studied were the types of solvent (acetone, chloroform and ethanol), solvent-to-solid ratio (2.0 ml/g to 10.0 ml/g) and raw material particles size (0.5 mm to 5.0 mm in diameter). The theoretical maximum yield of rotenoids resin in dried roots obtained from the optimization phase was 12.26 % (w/w) and 5.99 % (w/w) for the rotenone. The multiple response variables analysis have consistently verified the theoretical results in the range of 3.62 ml/g to 4.72 ml/g (solvent-to-solid ratio) and 0.83 mm to 1.41 mm in diameter (raw material particles size) using the acetone extract. The biological activity (LC50) value of rotenoids resin was indirectly correlated to the optimum processing parameters due to inconsistency of rotenone content (mg) and the low value of LC50 which was less than 100 ppm for all treatments. This is due to the presence of other constituents in the rotenoids resin (tephrosin, 12aÃŸ-rotenolone and deguelin) which contributed to the low LC50 values. The optimization of the processing parameters resulted in an increase of yield of rotenoids resin but reduced yield of rotenone